2002
DOI: 10.1148/radiol.2243011300
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure of CHO-K1 Cells to a 10-T Static Magnetic Field

Abstract: Strong (10-T) SMFs have no effect on cell growth, cell cycle distribution, or micronucleus frequency, but they may cause an increase in the micronucleus formation induced by 4-Gy x rays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 21 publications
3
81
1
Order By: Relevance
“…Long-term exposure to a static magnetic field alone did not affect micronucleus formation [2]. In X-ray-irradiated cells, exposure to a 1-T static magnetic field also did not affect micronucleus formation, but exposure to a 10-T static magnetic field resulted in a significant (p!0.05) increase in micronucleus formation induced after a 4-Gy exposure.…”
Section: Micronucleus Formationmentioning
confidence: 80%
See 1 more Smart Citation
“…Long-term exposure to a static magnetic field alone did not affect micronucleus formation [2]. In X-ray-irradiated cells, exposure to a 1-T static magnetic field also did not affect micronucleus formation, but exposure to a 10-T static magnetic field resulted in a significant (p!0.05) increase in micronucleus formation induced after a 4-Gy exposure.…”
Section: Micronucleus Formationmentioning
confidence: 80%
“…Clonogenic activity, DNA synthesis, cell cycle, and proliferation kinetics were not altered by exposure to the magnetic field and repetitive exposure to a static magnetic field up to 10 T exerted no effects on proliferation of human fetal lung fibroblast cells [1,2]. Cell cycle analysis of synchronized and nonsynchronized human fetal lung fibroblasts (HFLFs) cells did not reveal statistically significant differences between the cells exposed to 0.2, 1.0, or 1.5 T for 1 h/day for 5 consecutive days and control cells [3].…”
Section: Cell Proliferation and Cell Cycle Distributionmentioning
confidence: 95%
“…We also found no toxic effect on the ADSCs in this study. There may be concern that a high magnetic field can cause damage to the human body; however, reports indicated that static EMF from 0.3 T up to 1 T for more than 8 h/day did not have deleterious effects (25,(27)(28)(29). Even though the World Health Organization is concerned about the in vivo and in vitro effects of high EMF of more than 1 T, there is no definite evidence that high EMF will lead to damage in vivo and in vitro (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…SMFs alone do not have a lethal effect on the basic properties of cell growth and survival under normal culture conditions (Nakahara et al, 2002;Sakurai et al, 2009). Most studies have also suggested that SMFs do not affect cell proliferation (Hiraoka et al, 1992) or influence the cell cycle.…”
Section: Introductionmentioning
confidence: 99%